A synthetic development of tetrazines as ligands in Group 8 coordination complexes - Cooke, Gareth (Trinity College (Dublin, Ireland). School of Chemistry, 2009)
Chapter 1 describes the synthesis and characterization of a number of novel pyridazinecentred ligands prepared from substituted tetrazines. The use of these compounds as precursors for planar nitrogen containing graphite-type molecules is then discussed; specifically via cyclodehydrogenation.
Keywords: Chemistry, Ph.D.; Ph.D. Trinity College Dublin.